Athletes and supplements: Prevalence and perspectives - Garthe, I.; Maughan, R. J. (International Journal of Sport Nutrition and Exercise Metabolism, 2018)
In elite sport, where opponents are evenly matched, small factors can determine the outcome of sporting contests. Not all athletes know the value of making wise nutrition choices, but anything that might give a competitive edge, including dietary supplements, can seem attractive. Between 40% and 100% of athletes typically use supplements, depending on the type of sport, level of competition, and the definition of supplements. However, unless the athlete has a nutrient deficiency, supplementation may not improve performance and may have a detrimental effect on both performance and health. Dietary supplements are classified as a subcategory of food, so manufacturers are not required to provide evidence of product safety and efficacy, nor obtain approval from regulatory bodies before marketing supplements. This creates the potential for health risks, and serious adverse effects have been reported from the use of some dietary supplements. Athletes who compete in sports under an anti-doping code must also realize that supplement use exposes them to a risk of ingesting banned substances or precursors of prohibited substances. Government systems of regulations do not include specific laboratory testing for banned substances according to the WADA list, so a separate regulatory framework to evaluate supplements for their risk of provoking a failed doping test is needed. In the high-performance culture typical of elite sport, athletes may use supplements regardless of possible risks. A discussion around medical, physiological, cultural, and ethical questions may be warranted to ensure that the athlete has the information needed to make an informed choice.